Comparison of tensile properties between nanotwinned and nanograined CuAl alloys. (May 2018) - Wang, J.J.; Tao, N.R.
Abstract: Both nanotwinned and nanograined samples were prepared in a CuAl alloy by means of plastic deformation. Tensile tests showed that the nanotwinned sample exhibits a high yield strength of ~357 MPa and a considerable uniform elongation of 18% while the nanograined sample has ultra-high strength of ~758 MPa with a very limited uniform elongation of 1.4%. The lower yield strength and higher ductility in the nanotwinned sample were discussed based on its deformation mechanism. Graphical abstract: Unlabelled Image